A first look into the influence of triathlon wetsuit on resting blood pressure and heart rate variability - A Prado; J Dufek; J Navalta; N Lough; J Mercer (Termedia Publishing House, 2016)
The purpose of this study was to investigate the effects of wearing a wetsuit on resting cardiovascular measures (blood pressure (BP), heart rate variability (HRV)). The influence of position (upright, prone) and wetsuit size were also explored. Participants (n=12 males, 33.3±12.1 years) had BP and HRV measured during six resting conditions: standing or prone while not wearing a wetsuit (NWS), wearing the smallest (SWS), or largest (LWS) wetsuit (based upon manufacturer guidelines). Heart rate was recorded continuously over 5-mins; BP was measured three times per condition. HRV was represented by the ratio of low (LF) and high (HF) frequency (LF/HF ratio); mean arterial pressure (MAP) was calculated. Each dependent variable was analyzed using a 2 (position) x 3 (wetsuit) repeated measures ANOVA (α=0.05). Neither HRV parameter was influenced by position x wetsuit condition interaction (p>0.05) and MAP was not influenced by position (p=0.717). MAP and LF/HF ratio were both influenced by wetsuit condition (p<0.05) with higher during SWS than NWS (p=0.026) while LF/HF ratio was lower during SWS compared to NWS (p=0.032). LF/HF ratio was influenced by position being greater during standing vs. prone (p=0.001). It was concluded that during resting while on land (i.e., not submerged in water), wearing a small, tight-fitting wetsuit subtlety altered cardiovascular parameters for healthy, normotensive subjects.